Hemming Flames - Murphy, Patricia Colleen, 1970- (Book collections on Project MUSE., 2016)
"Winner of the 2016 Swenson Poetry Award, this collection explores themes of pain and loss as they emerge especially within a dysfunctional family. Includes a foreword by Stephen Dunn, American poet, teacher, and essayist, who was the judge for the 2016 award"--Provided by publisher.